2009
DOI: 10.1093/humrep/dep363
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratios do not serve as anatomical evidence of prenatal androgen exposure in clinical phenotypes of polycystic ovary syndrome

Abstract: Women with PCOS do not demonstrate finger length patterns that are consistent with increased prenatal androgen exposure. These findings do not preclude a role for prenatal androgens in the development of PCOS; however, low 2D:4D are not a characteristic of PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 43 publications
3
38
3
Order By: Relevance
“…Lujan ME et al [16], concluded that women with PCOS do not demonstrate finger length patterns that are consistent with increased prenatal androgen exposure and precluded that digit ratios measured by Vernier callipers do not serve as anatomical evidence of prenatal androgen exposure in PCOS which contradict our and Cattrall results. In her study collectively, women with PCOS tended to be slightly older (P = 0.068), of greater body mass index (BMI; P < 0.001), and had larger waist circumferences (P < 0.001) and reported longer menstrual cycles (P < 0.001) compared with controls.…”
Section: Digit Ratio (2d:4d): a Potential Anatomical Biomarker For Prcontrasting
confidence: 71%
See 2 more Smart Citations
“…Lujan ME et al [16], concluded that women with PCOS do not demonstrate finger length patterns that are consistent with increased prenatal androgen exposure and precluded that digit ratios measured by Vernier callipers do not serve as anatomical evidence of prenatal androgen exposure in PCOS which contradict our and Cattrall results. In her study collectively, women with PCOS tended to be slightly older (P = 0.068), of greater body mass index (BMI; P < 0.001), and had larger waist circumferences (P < 0.001) and reported longer menstrual cycles (P < 0.001) compared with controls.…”
Section: Digit Ratio (2d:4d): a Potential Anatomical Biomarker For Prcontrasting
confidence: 71%
“…The precise aetiology of PCOS is unknown, but there is strong evidence that it is largely a genetic disease [15]. However variable exposure to prenatal androgens may be responsible for the spectrum of endocrine and metabolic disturbances characteristic of this syndrome [16][17]. PCOS produces symptoms in approximately 5-10% of women of reproductive age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total testosterone was measured by isotope dilution liquid chromatography tandem mass spectrometry as previously described (27). Intra- and interassay coefficients of variation were <10% for both assays.…”
Section: Methodsmentioning
confidence: 99%
“…Women born from opposite sex-twins, for example, do not display an increased prevalence of PCOS-like features, although presumably they share a prenatal environment with a male co-twin that increases their exposure to testosterone 15 . Using relative finger length as an anatomical marker of in utero androgen exposure, some 1617 , but not all 1819 , PCOS women have altered length of the second finger relative to the fourth finger as a male characteristic that correlates with hyperandrogenism and ovarian volume (Table 1) 1820 . Adult female rhesus monkeys with PCOS-like features induced by early-to-midgestation testosterone excess also exhibit alteration of the same finger length ratio, implying an association between PCOS and finger length mediated by prenatal androgen excess 21 .…”
Section: Endocrine Antecedent To Pcosmentioning
confidence: 99%